Digitalization With Compassion - Isbahi, Muhammad Baiqun; Zuana, Muhammad Mujtaba Mitra; Toha, Mohamad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The rapid growth of the digital economy provides vast opportunities for entrepreneurship but often overlooks ethical and communal dimensions rooted in local traditions. In Muslim communities, economic activities are guided by principles such as fairness (ʿadl), mutual assistance (taʿāwun), and trustworthiness (amānah), which can serve as a moral foundation for digital transformation. This study examines how Islamic economic values can be embedded into the global digital marketplace as a model of compassionate digitalization. Using a qualitative ethnographic approach, data were collected through interviews and observations of Muslim entrepreneurs engaged in e-commerce while practicing local ethical values. Thematic analysis identified patterns of adaptation that integrate Islamic ethics into digital business models. Findings reveal that aligning digital platforms with Islamic principles fosters inclusive prosperity, trust, and tolerance. The study concludes that embedding Islamic ethics into digital business promotes a human-centered, sustainable marketplace by balancing innovation with moral and social responsibility